Thermal variation in human temporal bone using rigid endoscope - Thales Xavit Souza e Silva; Aline Bruno Figueiredo Nicolau; Marcos Luiz Antunes (Brazilian Journal of Otorhinolaryngology, 2024)
Objective: Compare thermal variation in the region of the External Acoustic Canal (EAC) and the Round Window (RW) using different rigid endoscopes and light sources in human temporal bones. Method: This is an analytical experimental study using human temporal bones. Thermal variation was assessed during ten minutes, using a thermometer in the region of the EAC and the RW of two temporal bones, right and left. We used three different endoscopes (0° 4-mm, 0° 3-mm and 30° 4-mm) and five intensity/type light source (Halogen 100%, LED 50%, LED 100%, Xenon 50% and Xenon 100% with the same endoscope light fiber. Results: We found temperature elevations in the EAC and RW in all measurements. Larger caliber endoscopes (4-mm) and light sources at 100% intensity generated higher temperatures, slightly higher in halogen and xenon. The 30° endoscopes tended to put more heat on structures, with little difference in most measurements. We identified greater temperature variations in the EAC of the right and left temporal bones compared to the RW overall. The highest temperature acquired in the present study was in the EAC of the temporal bone with a 4-mm and 30° endoscope, using xenon light source (intensity of 100%), with an increase of 4.51 °C. Conclusion: The type of endoscope and light source can influence the thermal variation and the risk of tissue injury during endoscopic ear surgery. Larger endoscopes with xenon and halogen light sources at maximum intensity generate more heat. Level of evidence: 5.